Design and Evaluation of a 4-Way Oracle GoldenGate Replication Architecture for Hybrid Cloud Environments - Karuppusamy Gopalan (International Journal of Intelligent Systems and Applications in Engineering, 2025)
In the era of hybrid cloud adoption, enterprises face significant challenges in maintaining data consistency, high availability, and operational continuity across geographically dispersed and heterogeneous environments. This study presents a novel implementation of 4-way active-active Oracle GoldenGate replication across on-premises and multi-cloud platforms, enabling real-time data synchronization, conflict resolution, and automated failover mechanisms [1][2]. The architecture interconnects four nodes—two on-premises and two cloud-based (Azure)—to deliver seamless data replication with less lag, ensuring transactional integrity and zero-downtime operations for critical enterprise applications. Key innovations include the use of Oracle GoldenGate Microservices Architecture, integration with cloud-native services [5], and deployment of Conflict Detection and Resolution (CDR) techniques to handle bi-directional updates in a multi-master configuration [2][3]. Experimental evaluation demonstrates that the proposed system achieves high throughput, minimal replication lag, and robust failover capabilities under diverse workloads and simulated failure conditions [6][7]. The results validate the effectiveness of the 4-way replication strategy in supporting disaster recovery, data sovereignty compliance, and cross-region data access in a hybrid cloud setting. This work contributes to the field of cloud database management by offering a scalable and resilient model for enterprise-grade data replication, applicable to sectors demanding high availability such as healthcare, finance, and e-commerce.